Root Growth in Single Shoots Tabah Bamboo Eye Cuttings (Gigantochloa nigrociliata Kurz) Using Auksin IBA (Indole Butyric Acid) and Growing Media - Abdul Jafar Maring; Mansur Ma’shum; Bambang Budi Santoso (Pascasarjana, Mataram University, 2023)
Tabah Bamboo has potential that needs to be developed both in the food sector, industry and environment. This type can be processed into food ingredients worth exporting, especially bamboo shoots. To meet the needs of raw materials need to multiply plants in the field through nurseries one of them using stem cuttings. Root growth is an indicator of the success of nurseries using cuttings. The research was conducted at KHDTK Rarung, Central Lombok from October 2020 until January 2021. The purpose of the study was to determine the influence of concentration IBA (Indole Butyric Acid), growing media, and long soaking cuttings in the solution of IBA concentration on the growth of cutting roots. The results showed that the best root emergence time occurred in a combined concentration of 400mg.1-l IBA and soil media +cocopeat + manure. Each factor independently has a noticeable effect on the number of roots. Concentration of 400mg.1-l IBA, soaking length of 1 hour, and soil media+cocopeat+manure result in a better number of roots. Combination concentration of 400mg.1-l IBA and a 1-hour soaking length result in better root length at 43 hst, while a combined concentration of 400mg.1-l IBA and soil media + cocopeat + manure produce better root length at the age of 50 hst and 57 hst. Combination concentration of 400mg.1-l IBA, soaking length cuttings 1 hour, and soil media + cocopeat + manure produce fresh weight and dry roots best